2015
DOI: 10.1016/j.joca.2015.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Synovial mesenchymal stem cells promote healing after meniscal repair in microminipigs

Abstract: Transplantation of synovial MSCs promoted healing after meniscal repair with induction of synovium into the longitudinal tear in the avascular zone of meniscus in pigs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
100
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 38 publications
3
100
1
Order By: Relevance
“…Previously, it has been suggested that the potential of synovial MSCs can be affected by the presence of cartilage injury and the period between the onset of pain and date of surgery [28]. However, in this study, there was no significant difference in growth potential despite varied time frame between onset of pain and date of surgery for both the knee and the hip joints for our patients.…”
Section: Discussioncontrasting
confidence: 66%
“…Previously, it has been suggested that the potential of synovial MSCs can be affected by the presence of cartilage injury and the period between the onset of pain and date of surgery [28]. However, in this study, there was no significant difference in growth potential despite varied time frame between onset of pain and date of surgery for both the knee and the hip joints for our patients.…”
Section: Discussioncontrasting
confidence: 66%
“…Mesenchymal stem cells derived from synovial membrane (synovial MSCs) are a candidate cell source for regenerative medicine of cartilage [13] and meniscus [46] due to their great chondrogenic ability [7, 8]. In clinical practice, the transplantation of autologous synovial MSCs for ten patients with a symptomatic single cartilage lesion in the knee joints was shown to be effective in terms of magnetic resonance imaging (MRI) and patient-oriented outcome scoring [9].…”
Section: Introductionmentioning
confidence: 99%
“…While MSCs have been employed in many of the cellbased meniscal repair studies, 37,38 meniscus-derived cells could be a good cell source because these cells showed strong proliferative and fibrocartilaginous differentiation capacities, as reported in previous studies. 29,30 Also, regarding the method of cell isolation, we isolated MFCs from small pieces of meniscal tissue without collagenase, using a previously published method.…”
Section: Discussionmentioning
confidence: 80%